PERANAN DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BENGKALIS DALAM PENEMPATAN TENAGA KERJA LOKAL DI PT. WAHANA KARSA SWANDIRI KECAMATAN MANDAU - Teguh Handika; Sufian Hamim (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
The pu rpose of this study was to determine the role of the Manpower Office in the placement of workers.This research was a qualitative descriptive study. The focus of this study is the Role of the Manpower Office in the placement of local workers: Job Seekers Job Vacancies Job Market Information Mechanism of Interagency Institution Employment Placement, supporting factors and inhibiting factors in the placement of workers in Mandau Subdistrict. The primary data source in this study consisted of the key informants who were the Secretary of the Bengkalis Regency Manpower Office. While the informants were the Head of the Field and the Head of the Local Manpower Placement Section of the Bengkalis Regency Manpower Office, there were 2 people obtained through the Purposive Sampling method. As for the primary data source through the Accidental Sampling method, the job seekers who have been placed by the Bengkalis Regency Manpower Office are collected through literature, observation, interviews and field research. Data analysis technique used is an interactive model consisting of data condensation, data presentation and conclusion drawing.Based on the results of the study, it can be seen that the role of the Manpower Office in the Bengkalis Regency Manpower Placement is that there are still many registered workers who do not have job skills and lack of interest in existing job vacancies, job vacancies that are still lacking, information on labor market information that is lacking maximum, There is still a lack of knowledge about the mechanism between work both from companies and job seekers in the placement of labor, Lack of understanding about labor placement institutions.